The role of long-term inflation expectations for the transmission of monetary policy shocks - Max Diegel; Dieter Nautz (Freie Universität Berlin, School of Business & Economics, 2020)
This paper empirically investigates the role of long-term inflation expectations for the monetary transmission mechanism. In contrast to earlier studies, we confirm that U.S. long-term inflation expectations respond significantly to a monetary policy shock. In line with a re-anchoring channel of monetary policy, we find that long-term inflation expectations play an important role for the transmission of monetary policy shocks to the rate of inflation. Our results are robust with respect to the identification strategy and alternative monetary policy indicators applied during the zero lower bound period.
urn:nbn:de:kobv:188-refubium-28829-9
Keywords: E31; E52; C32; 330; Long-Term Inflation Expectations; Monetary Policy; Structural Vector Autoregression; Sign and Zero Restrictions